2017
DOI: 10.1167/iovs.17-22171
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Layer Thickness Changes During Dark Adaptation Observed With Ultrahigh-Resolution Optical Coherence Tomography

Abstract: PurposeTo examine outer retinal band changes after flash stimulus and subsequent dark adaptation with ultrahigh-resolution optical coherence tomography (UHR-OCT).MethodsFive dark-adapted left eyes of five normal subjects were imaged with 3-μm axial-resolution UHR-OCT during 30 minutes of dark adaptation following 96%, 54%, 23%, and 0% full-field and 54% half-field rhodopsin bleach. We identified the ellipsoid zone inner segment/outer segment (EZ[IS/OS]), cone interdigitation zone (CIZ), rod interdigitation zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 41 publications
(51 reference statements)
3
76
1
Order By: Relevance
“…This observed elongation of foveal/parafoveal cones, and the dependence of elongation on stimulus intensity, is qualitatively consistent with previously reported elongation of peripheral cones using full-field OCT with computational aberration correction [5]. We hypothesize that the mechanism of this elongation is osmotic swelling of the outer segment, as it is consistent with observations made using conventional OCT images in human rods [4] and mouse rods, in which elongation is suppressed in mice lacking transducin [17]. In addition to OS elongation, changes in the axial morphology of cones were observed subsequent to the stimulus flash.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This observed elongation of foveal/parafoveal cones, and the dependence of elongation on stimulus intensity, is qualitatively consistent with previously reported elongation of peripheral cones using full-field OCT with computational aberration correction [5]. We hypothesize that the mechanism of this elongation is osmotic swelling of the outer segment, as it is consistent with observations made using conventional OCT images in human rods [4] and mouse rods, in which elongation is suppressed in mice lacking transducin [17]. In addition to OS elongation, changes in the axial morphology of cones were observed subsequent to the stimulus flash.…”
Section: Resultssupporting
confidence: 91%
“…exams, are effective after extensive pathological changes, but not in the earliest stages of disease. Adaptive optics (AO) flood imaging [1], conventional optical coherence tomography (OCT) [2,3,4], and full-field OCT [5] have revealed changes in the human photoreceptor outer segment (OS) in response to visible stimuli. Here, we describe an OCT imaging system that leverages the three-dimensional cellular resolution of AO and OCT [6,7] and the speed of a Fourier-domain mode-locked (FDML) laser [8,9].…”
mentioning
confidence: 99%
“…Recent investigations in mice and humans with OCT have shown that ROS and/or cone OS elongate in response to stimuli that bleach substantial fractions of their rhodopsin. [42][43][44][45] In mouse rods, this elongation has been established to be driven by phototransduction because it requires expression of the rod Gprotein transducin. 42 Given the capability of OCT to measure submicrometer ROS length changes after suitable averaging and analysis, 42 we undertook an investigation to determine whether OCT could also be used to measure diurnal ROS length changes arising from disc shedding and renewal.…”
mentioning
confidence: 99%
“…47 The term has been recently adopted by other investigators 48 (Pandiyan et al; IOVS 2019;60; ARVO E-Abstract 1426) for the paradigm of using NIR OCT to measure bleaching-induced backscattering and/or elongation changes in the eye in vivo noninvasively. [42][43][44][45]49 We think the term deserves general adoption in vision and ophthalmology, as ORG draws an instructive parallel to the ERG, which has long been used to assess retinal function in vivo. Specifically, the ORG, like the ERG, comprises multiple components arising from distinct cells and mechanisms.…”
mentioning
confidence: 99%
“…For example, implementation of APM-AO-OCT should lead to broader application of OCT to brain structural imaging 60,61 where the presence of speckle in images remains a major obstacle. Finally, thanks to the improvement in the visualization of subcellular structure, APM-AO-OCT should enable a more precise localization and quantification of retinal optophysiological signals, which provide non-invasive, label-free measurement of photoreceptor function [62][63][64]…”
Section: Future Directionsmentioning
confidence: 99%